Caliber and fitness of the axillary artery as a conduit for large‐bore cardiovascular procedures. Issue 1 (11th November 2017) - Arnett, Daniel M.; Lee, James C.; Harms, Michael A.; Kearney, Kathleen E.; Ramos, Mario; Smith, Bryn M.; Anderson, Emily C.; Tayal, Rajiv; McCabe, James M.
Abstract: Objectives: We sought to describe the caliber and vascular health of the subclavian and axillary arteries as related to their potential utilization in complex cardiovascular procedures. Background: Patients referred for advanced catheter‐based therapies frequently have lower extremity peripheral vascular disease that may prohibit the use of large bore arterial catheters. Utilization of the upper extremity peripheral vasculature is rarely considered as an alternative access strategy. This may be due in part to a lack of familiarity with the thoracic vasculature. Methods and Results: 208 consecutive patients undergoing routine CTA prior to transcatheter aortic valve replacement were retrospectively evaluated in a systematic analysis of upper and lower extremity vasculature. Minimal luminal diameters (MLDs) for the axillary arteries and iliofemoral arteries were 6.0 ± 1.1 mm and 6.6 ± 1.8 mm respectively. Compared to the iliofemoral arteries, the axillary arteries demonstrated substantially lower rates of significant stenosis (2% vs. 12%, p  < 0.01) and significantly lower rates of moderate to severe calcification disease (9% vs. 64%, p  < 0.01). Diabetes and tobacco use were independently associated with smaller axillary artery caliber by MLD ( p  < 0.01) but not with significant stenotic disease. Conclusions: The axillary arteries are slightly smaller but less frequently diseased than the corresponding iliofemoral vessels.